PENGEMBANGAN BUKU SUMBER BELAJAR MENGENAL BUDAYA JAWA BARAT UNTUK MENINGKATKAN LITERASI BUDAYA SISWA PADA MATA PELAJARAN IPS DI SEKOLAH DASAR - Nursita, Neng Hilda; Kurnia, Ira Restu (Universitas Muhammadiyah Tapanuli Selatan, 2023)
Developing a learning resource book about West Javanese culture is one way to increase students' cultural literacy. Make students get to know the culture of West Java, especially in social studies learning.The purpose of this research is; (1) understand the meaning of cultural literacy; (2) apply the understanding of cultural literacy; (3) describe the effectiveness of the book as a source of learning about the culture of West Java. This research was conducted in May-August 2023 and was conducted in class IV at SDN Sukadami 04 Cikarang with a total of 43 students. The method used in this study is Research and Development (RD) and uses the ADDIE development model with 5 stages.The results showed that the source book for learning about West Javanese culture which had been developed based on media experts got a percentage score of 90% with a very valid category, then validation by material experts got a percentage score of 80% with a valid category, and then by linguists got percentage score of 72% with a valid category. The development test conducted on 43 grade IV students obtained a percentage score of 95% in the very practical category, the test measuring the effectiveness analysis conducted on 43 grade IV students obtained a percentage score of 93% in the very effective category, and then the teacher's assessment obtained a percentage score of 92. 5% in the very practical category. Based on the results of the data acquisition, it shows that the development of learning resource books about West Java culture is to increase students' cultural literacy in social studies subjects in elementary schools.